Comparative analysis between european registration systems and guidelines of the brazilian registration associated with the FIG parameters - Prieto, Raidel Báez; Lima, Carla Luciane; Padilha, Victor Luis; Kinas, Priscila Natasha; Oliveira, Francisco Henrique de (Ciência e Natura, 2020)
This work aims to contribute to the expansion of knowledge about european cadastre systems and brazilian cadastre guidelines associated to the parameters of the FIG, seeking to promote the enrichment of discussions on this topic through a comparative analysis considering legal, cartographic, economic and social aspects. According to the data collected, it was possible to establish similarities and differences between the european and brazilian cadastre systems, discussing contributions that international experience could give in the effective regulation of these guidelines in Brazil. Therefore, in order to reach an integrated management of the territory, this work contemplates a set of public policies articulated along with its instrumental components, intending to have the Territorial Multipurpose Cadastre (CTM) applied in its complete form.